Introduction to management science - Cook, Thomas M., 1940- 4 0 16; 1946- Russell, Robert A.; 5 (Englewood Cliffs, N.J. : Prentice Hall International, Inc., 1993)
Introduces some of the new tools and technology that have been developed to help management in the decision-making process.
Includes bibliographical references and index.
Young Adult.
Keywords: 2 -- 0; 6; Mathematical models. -- Management;Operations research.;Management science. -- 20; 20; 2